Rejuvenating Economic Empowerment: A Study on Women-led Entrepreneurship in Molasses Production in Manipur - MD FAIZUL HAQUE; DR. SURESH SAH (Innovative Research Thoughts, 2023)
Women in Manipur have exhibited their entrepreneurial spirit by engaging in various occupations to secure their livelihoods. Historically, some women were involved in selling locally-made liquor, although this came with the burden of societal stigma and discrimination. Subsequently, a group of women entrepreneurs ventured into molasses production, paving the way for their own success stories and inspiring others to pursue better earning opportunities. This research delves into the socio-economic landscape of Scheduled Caste (SC) women engaged in molasses production in Kakching, Manipur. The study aims to assess the current status of women's participation in molasses entrepreneurship, evaluate the potential for sustainable economic growth, identify challenges faced by women in successfully conducting their trade, and explore the prospects presented by India's Look East Policies. The study concludes by offering insightful recommendations based on the research findings.